ANALYSIS OF THE RESULTS OF TREATMENT OF 93 PATIENTS WITH POST-COVID THROMBOSIS OF THE CAVERNOUS SINES IN THE CONDITIONS OF THE DEPARTMENT OF PURULENT SURGERY. - Kasimov, Ulugbek (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Complications of the transferred COVID-19 are accompanied by the development of such complications as cavernous sinus thrombosis. The paper analyzes the results of treatment of 93 patients treated in the Department of Purulent Surgery and Surgical Complications of Diabetes Mellitus. The analysis showed that only in 31.2% of cases, patients were discharged with positive dynamics for further treatment and observation on an outpatient basis, while more than half of the patients 62 (66.7%) were taken home. It is necessary to revise the tactics of managing patients with post-covid manifestations of cavernous sinus thrombosis. Recommendations should reflect specific criteria for when expectant management is needed and when emergency surgery is needed, as another outbreak of the virus with its new mutating strains is not ruled out, where specialists should be ready to manage these patients.